Infeksi Menular Seksual - Anisa Putri Utami; Ika Restu Kaeksi; Nisa Wahyuningsih; Liss Dyah Dewi Arini (STIKes Ibnu Sina Ajibarang, 2025)
Sexually Trnsmitted Infections (STIs) are a group of diases that are transmitted through sexual contact, whether vaginal, anal or oral, which are caused by various pathogenis agents such as bacteria, viruses, parasites and fungi. STIs include diseases such as gonorrhea, syphilis, chlamydia, trichomoniasis, genital herpes, human papillomavirus (HPV), and HIV/AIDS. This disease can attack anyone who is sexually active, especially those who do not practice safe sexual relations. Symptoms of STIs vary greatly, ranging from asymptomatic to sores in the genital area, abnormal vaginal discharge, pain when urinating, to serious complications such as infertility, ectopic pregnancy, or cervical cancer.